Analisis Resiko Postpartum Blues pada Ibu Nifas di RSUD Jati Padang Jakarta Selatan - Aulya, Yenny; Amalia, Atika; Syamsiah, Siti (Universitas Baiturrahim, 2024)
According to the World Health Organization, WHO (2018), the general prevalence of postpartum blues in the world population is 3-8%, with 50% of cases occurring in the productive age group, namely 20-50 years. WHO also states that postpartum blues affects approximately 20% of women and 12% of men at some time in life.Quantitative research using observational-analytic methods based on numbers in measuring variables and drawing conclusions from the facts studied. The research design was measured using cross-sectional by using purposive sampling technique for sampling and obtained 59 respondents in this study. The research instruments were the EPDS (Edinburg Postnatal Depression Scale) questionnaire and questionnaire. Based on the results of non-parametric statistical analysis using the Chi Square test P-value 0.000 <0.05, which means there is a relationship between age, parity, pregnancy status, employment, husband's support and family support on the incidence of postpartum blues in postpartum women at Jati Padang Hospital in 2023. There is a relationship between age, parity, occupation, husband's support, and family support on the incidence of postpartum blues in postpartum women. It is hoped that postpartum mothers, families, and health workers can collaborate in paying attention to the psychological condition of the mother after giving birth